2007
DOI: 10.1146/annurev.energy.32.041806.143704
|View full text |Cite
|
Sign up to set email alerts
|

Women, Water, and Development

Abstract: That women play a central role in the provision, management, and safeguarding of water is one of the four internationally accepted principles of water management. This principle is especially important for the developing world where millions of women lack access to water for their basic needs. The objectives of this chapter are to summarize what is known about women with respect to water and about water with respect to women as well as to provide a sense of the current debates around these themes. A review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(86 citation statements)
references
References 65 publications
2
83
0
1
Order By: Relevance
“…Time spent may be a better indicator of the burden of fetching water in some locales. In densely populated areas, improved water sources might be nearby but waiting in line can take an hour or more (Ray, 2007). Women's workload in agricultural societies often exceeds that of men (Mpetsheni, 2001), and collecting water and heating fuel are two of the most time-consuming activities.…”
Section: Measuring Water Fetching and Its Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time spent may be a better indicator of the burden of fetching water in some locales. In densely populated areas, improved water sources might be nearby but waiting in line can take an hour or more (Ray, 2007). Women's workload in agricultural societies often exceeds that of men (Mpetsheni, 2001), and collecting water and heating fuel are two of the most time-consuming activities.…”
Section: Measuring Water Fetching and Its Effectsmentioning
confidence: 99%
“…Research on the multiple impacts of fetching water on women's lives is incomplete, and the lack of gender-disaggregated data -as well as data on related health risks -obscures a more complete understanding of the unequal burden (Ray, 2007). Attendees at a recent Expert Group Meeting organized by the UN-Water Decade Programme on Capacity Development stressed the need for gender-disaggregated data (Seager, 2008).…”
Section: Implications For Researchmentioning
confidence: 99%
“…These findings suggest that the reported importance of networks to women in particular, as indicated in other studies (Berry, 1989;Ray, 2007;Young, 1993), may not always translate into benefits to all women, only those of certain class groups. This finding further suggests that women in the study villages may require both networks and some basic level of household assets in order to avoid reactive responses.…”
Section: Resultsmentioning
confidence: 56%
“…For example, to secure access to water, women use informal social networks in the absence of formal rights (Ray, 2007). Along similar lines, other research has suggested that women are more likely to invest their time and energy into strengthening social networks at the expense of building productive capital, with the aim of securing access to resources especially during times of scarcity (Berry, 1989).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation